2022
DOI: 10.1021/acssuschemeng.2c05430
|View full text |Cite
|
Sign up to set email alerts
|

Low Carbon Alkali-Activated Slag Binder and Its Interaction with Polycarboxylate Superplasticizer: Importance of Microstructural Design of the PCEs

Abstract: To investigate the role of polycarboxylate superplasticizers in a low carbon alkali-activated slag (AAS) system, two series of APEG and HPEG polycarboxylate ethers (PCEs) with different anionicities were designed and synthesized in this study. The resulting PCE samples were characterized via size exclusion chromatography, anionic charge titration, and high-resolution 13C NMR spectroscopy. The paste and mortar spread flow tests suggest that in AAS, the synthesized HPEG PCEs exhibit superior dispersing performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The actual molar ratio of EPEG to AA can be quantitatively calculated by determining the total area of the H characteristic peak signals in both the PCE main chain and PEG side chain. , Importantly, it is found that the actual molar ratio of EPEG to AA under photoinitiation is close to the feeding molar ratio in Table S4. The actual monomer ratio of the LPCE1 structure is 1:4.13, which closely approximates the theoretically designed ratio of 1:4.…”
Section: Resultsmentioning
confidence: 99%
“…The actual molar ratio of EPEG to AA can be quantitatively calculated by determining the total area of the H characteristic peak signals in both the PCE main chain and PEG side chain. , Importantly, it is found that the actual molar ratio of EPEG to AA under photoinitiation is close to the feeding molar ratio in Table S4. The actual monomer ratio of the LPCE1 structure is 1:4.13, which closely approximates the theoretically designed ratio of 1:4.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported commonly that PCE products that are unadsorbed on cement could substantially improve dispersion and flowability of cement due to their steric hinderance effect 82 . However, self‐polymerization of small monomers and presence of side products remain a major challenge in the PCE production process 83 …”
Section: Synthetic Concrete Water Reducersmentioning
confidence: 99%
“…In practical engineering application, it was found that although the water reduction rate of ester-containing PCEs was not prominent, it had wide adaptability with different cements, and the concrete mixed with it had excellent workability [19]. Although the water-reducing rate of ether-containing PCEs was higher, it often caused segregation and bleeding of concrete due to its sensitive dosage, which seriously affected the workability of concrete [20]. Therefore, PCEs with different molecular structures might play different roles in practical applications.…”
Section: Introductionmentioning
confidence: 99%